The Frequency of and Contributing Factors to the Psychological Abuse of Older People in Nursing Homes in Turkey - GÜR, KAMER; EROL, SAİME (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: This study investigated the frequency of the psychological abuse of older people in nursing homes and contributing factors. Methods: The population for this methodological and descriptive study was 161 elderly individuals living in two nursing homes in Istanbul. The data were collected using Barthel's Index, the Standardized Mini Mental Test (SMMT) and the Elders' Psychological Abuse Scale (EPAS). The scale's reliability was tested using the Kuder-Richardson Formula 20 (KR-20) and test-retest analysis. Its validity was tested using the Content Validity Index (CVI) and concurrent validity. The frequency of abuse is presented using numbers, percentages, and means. The relationship between the independent variables and abuse was evaluated using the t-test and Kruskal-Wallis variance analysis. Results: The participants' mean age was 73.5 years (42.2% were older than 80 years); 44.7% were female. The mean scores were 5.57 +/- 4.12 on the EPAS and 89.13 +/- 17.13 on Barthel's Index. The KR-20 reliability coefficient for the scale was 0.80. The test-retest reliability was 0.97; p=0.000, and the content validity index was 90%. Of the participants, 14.3% were exposed to psychological abuse. Individuals with high dependency and low levels of income, education and mental capacity were exposed to psychological abuse more frequently (p <0.05). Conclusion: The Turkish version of the originally English EPAS is reliable and valid.
Keywords: Psychological abuse; older people; nursing homes; scale; ELDER ABUSE; RISK-FACTORS; ADAPTATION; PREVALENCE; NEGLECT